Nominal Debt and the Dynamics of Currency Crises - Giancarlo Corsetti; Bartosz Mackowiak (Yale University, Economic Growth Center, 2000)
We study the interaction of fiscal and monetary policies during a currency crisis in an economy with government nominal liabilities. We show that the stock and maturity of these liabilities are key determinants of the magnitude, timing and predictability of a devaluation. Among notable features of our model, monetary authorities defend the currency parity conditional on the level of the interest rate, rather than on the stock of international reserves; budget deficits need not be high before a currency crisis; post- devaluation inflation may exhibit little persistence, and money demand need not fall after the crisis.
Keywords: F31; F33; E58; 330; Währungskrise; Öffentliche Schulden; Abwertung; Währungsspekulation; Finanzpolitik; Geldpolitik; Theorie